Cyberbullying sebagai Praktik Kejahatan Berbahasa pada Akun Instagram Capres dan Cawapres Republik Indonesia 2024 - Andi Nurindah Sari; Nurlingga Ibrahim; Kurniawan (Indonesian Journal of Criminal Law, 2025)
Abstract. This study aims to examine the forms and patterns of cyberbullying as a language crime practice and describe the potential legal impact caused by cyberbullying as a language crime practice on the Instagram accounts of the presidential and vice presidential candidates of the Republic of Indonesia in 2024. This research adopts a qualitative method with a forensic linguistic approach. The analysis technique used includes data reduction, data presentation, and verification. The results show that there are various forms and patterns of cyberbullying that can be identified in several presidential and vice presidential candidate posts, ranging from flaming, harassment, and denigration. In addition, this study found that the practice of cyberbullying has the potential to cause serious legal implications, identified in the Criminal Code and Law of the Republic of Indonesia Number 1 of 2024 concerning amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE). The research emphasises the urgency of improving digital literacy and stricter law enforcement to address the problem amid Indonesia's political dynamics in 2024.